Analasis Supply Chain Management (SCM) Komoditas Gula Aren di Kota Perdagangan Kabupaten Simalungun - Afdillah Nur Aisyah Sinaga; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
Palm sugar prices can increase or decrease as a result of an imbalance between existing products and market demand. Palm sugar supply chain management is very influential on the availability and stability of palm sugar prices in the market. This study aims to determine the Supply Chain Management of palm sugar commodities in the City of Perdagangan, Simalungun Regency, which includes the flow of products, information, and finance, along with the level of efficiency. This research is included in qualitative research by seeking meaning, understanding, understanding, about a phenomenon. This research was conducted in the City of Perdagangan, Simalungun Regency for a period of one month, namely from June and obtained resource persons consisting of craftsmen/makers of palm sugar, collectors and retailers. The results show that supply chain management related to product flow, information flow, and financial flow in the palm sugar supply chain in the City of Perdagangan is efficient when viewed from the benefits of each channel.